The Utilization of Salt Painting Media to Develop Children's Fine Motor Skills - Munar, Asyiful; Rahma, Rahma; Prala, Hendri Wan (JOYCED: Journal of Early Childhood Education, 2024)
Fine motor development is one of the developments that can be honed in early childhood. Salt painting media is a medium that can develop children's fine motor skills. However, the fine motor skills of children at the IT Baitusshalihin Ulee Kareng Kindergarten in Banda Aceh are not yet fully developed. Most children still have difficulty using writing tools, imitating shapes, forming patterns, and cutting out patterns, and they even still have difficulty exploring various tools/media. This research aims to determine whether salt painting media can develop children's fine motor skills at the IT Baitusshalihin Ulee Kareng Kindergarten, Banda Aceh. The research sample was children aged 4-5 years which involved children from group A2 as the control class and A3 as the experimental class, totaling 15 children. This type of research is experimental using quasi-experimental analysis. This research used a pre-test-post-test control group design. Based on calculations using t-test statistics. Then using salt painting media can develop children's fine motor skills as obtained by t count > t table, namely 3.89 > 1.70 so that the alternative hypothesis Ha is accepted and the hypothesis H0 is rejected. Therefore, it can be concluded that the use of salt painting media can develop children's fine motor.